Choosing the right contraception - Chawarntunpipat, Pimpat; Jaisamrarn, Unnop; Santibenchakul, Somsook (Journal of Medicine and Health Sciences, 2022)
Abstract Choosing the right contraception is a crucial strategy to prevent unintended pregnancies. Appropriate contraceptive methods for each woman should be highly effective in preventing pregnancy, safe and with fewer side effects, and other benefits beside contraceptive benefits. In terms of contraceptive efficacy comparison, the Life table analysis is more appropriate than the Pearl index, because this index considers the time when women use contraceptives. Generally, reproductive-aged women are healthy, so the risk of using contraceptives are very low. However, women with medical diseases might pose a serious risk in terms of using contraception. Therefore, it was recommended that healthcare providers should take a detailed medical history, current medicine usage and to perform a physical examination to assess their risk in the use of each contraceptive method. The risks of using hormonal contraceptives, such as cardiovascular diseases, cerebrovascular diseases and deep vein thrombosis are rare, especially with modern, low-dose hormonal contraception. Healthcare providers should provide information about the common side effects of each contraceptive method and non-contraceptive benefit for clients. This information may help clients decide to initiate and continue their use of contraception.